Steady state heat transfer within a nanoscale spatial domain - Poletkin, Kirill V. (2012)
In this paper, we study the steady state heat transfer process within a spatial domain of the transporting medium whose length is of the same order as the distance, travelled by thermal waves before these waves are dissipated by thermal diffusion. In this study, the thermal conductivity is defined as a function of a spatial variable. This is achieved by analyzing an effective thermal diffusivity that is used to match the transient temperature behavior in the case of heat wave propagation by the result obtained from the Fourier theory. Then, combining the defined sizedependent